Personal Law and Property Rights of Hindu Woman in India - The Need for Codification - Thulaseedharan, Sindhu (Kathmandu School of Law Review, 2018)
In India, the familial relations of any citizen, including inheritance, are governed by law related to his or her religion, which came to be known as personal law. The property rights of Hindu woman from the vedic age reflected that daughter was given a share equal to that of a son, who in the later age of smritis ( traditional law) , came to inherit only in the absence of male issue. The nature of property of a Hindu woman, stridhanam (woman’s property) thus came to be distorted from absolute property right to ‘limited estate’ known as ‘woman’s estate’. That is, the property passed only to the next heirs of the last male owner of the female intestate. The legislations in the pre-independent India strengthened the position of Hindu woman. But the later laws limited her interest in property to the sense that she could alienate it for certain purposes only and the property possessed by her devolved on the heirs of her husband and not on her own heirs. The retention of testamentary power has further undermined gender-equality largely. Even at present, the Hindu Succession (Amendment) Act, 2005, allows existing property disputes to continue and does not affect rights that became vested prior to its implementation. Therefore, the codification of personal law on succession becomes the need of the hour, since the patriarchal norms retained in the law have to be dropped.